Investigation into bicycle crossings - Tay, Si Ting (2019)
Due to Singapore’s compact size, we have been facing land constraint issues over the decades. With little space and competing needs, it puts a limit as to how far we can further expand our road network. Therefore, the government and authorities have been actively encouraging the shift towards greener modes of transport to cut down on car ownership. Gradual success has been observed over the recent years as active mobility starts to gain popularity. As an increasing number of active mobility devices are seen on the streets today, there is a need to foster greater rider responsibility and encourage safe sharing of our paths and roads.